2013
DOI: 10.1645/12-37.1
|View full text |Cite
|
Sign up to set email alerts
|

Centrocestus formosanus(Heterophyidae): Human Infections and the Infection Source in Lao PDR

Abstract: In Lao People's Democratic Republic (PDR), we detected 7 patients infected with Centrocestus formosanus (1-122 adult specimens) after praziquantel treatment and purgation, together with several other trematode species including Opisthorchis viverrini and Haplorchis taichui. The patients were all men, 23-42 yr-of-age. Three subjects were from Vientiane Municipality and 1 each were from Khammouane, Saravane, Champassak, and Xiengkhouang Province. The patients had frequently eaten raw freshwater fish and were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…The number of circumoral spines of C. formosanus is 32 spines in most cases [1,18]. It is also similar to a previous study that reported 32 circumoral spines of C. formosanus [35]. This species differed from the related species; C. caninus which has 26–30 spines [6].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The number of circumoral spines of C. formosanus is 32 spines in most cases [1,18]. It is also similar to a previous study that reported 32 circumoral spines of C. formosanus [35]. This species differed from the related species; C. caninus which has 26–30 spines [6].…”
Section: Discussionsupporting
confidence: 79%
“…The worm was reported to be infected in humans in Taiwan, Japan, and Lao PDR [2,3]. It is distributed in many countries, i.e., Taiwan (China), Japan, the Philippines, India, Lao PDR, Mexico, and Brazil [35]. Centrocestus caninus is a closely related species to C. formosanus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O. viverrini is the causative agent of obstructive jaundice, pancreatitis, cholangitis, and cholangiocarcinoma (Choi et al, 2006). Moreover, C. formosanus has been reported causing diarrhea, epigastric pain and indigestion (Chai et al, 2013).…”
mentioning
confidence: 99%
“…Centrocestus formosanus is a small intestinal parasite of birds and mammals which has also been recorded in humans from Asia (Chai et al, 2013). The species was introduced into American continent in the 1950s (Martin, 1958) and it may be found in the USA, Mexico, Colombia, Venezuela and Brazil, nowadays (Pinto and Melo, 2011).…”
Section: Discussionmentioning
confidence: 99%